2015
DOI: 10.18314/gjct.v1i1.33
|View full text |Cite
|
Sign up to set email alerts
|

A Cocktail of Specific Inhibitors of HER-2, PI3K, and mTOR Radiosensitises Human Breast Cancer Cells

Abstract: Intrinsic tumour radioresistance limits the benefit of radiotherapy. Targeted treatment modalities that are singly effective for triple-negative breast cancer are lacking, partly due to paucity of relevant targets as they are devoid of the human epidermal growth factor receptor 2 (HER-2), progesterone receptor (PR), and oestrogen receptor (ER); or to resistance to single-target therapies as a consequence of cellular heterogeneity. Concomitant targeting of cell signaling entities other than HER-2, PR and ER may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
(41 reference statements)
3
3
0
Order By: Relevance
“…However, in the ER and PR positive MCF-7 cell line [10,11], inhibition of PI3K, mTOR and Bcl-2 results in less than 2-fold radiosensitisation. These findings are consistent with the radiosensitisation reported elsewhere for pre-treatment of cell cultures with a cocktail of HER2, PI3K and mTOR inhibitors [6]. The marginal radiosensitisation seen in the MCF-7 cells can be attributed to the fact that they are PI3K mutated, in contrast to their PI3K wild-type counterparts, MDA-MB-231 and MCF-12A [12,13].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…However, in the ER and PR positive MCF-7 cell line [10,11], inhibition of PI3K, mTOR and Bcl-2 results in less than 2-fold radiosensitisation. These findings are consistent with the radiosensitisation reported elsewhere for pre-treatment of cell cultures with a cocktail of HER2, PI3K and mTOR inhibitors [6]. The marginal radiosensitisation seen in the MCF-7 cells can be attributed to the fact that they are PI3K mutated, in contrast to their PI3K wild-type counterparts, MDA-MB-231 and MCF-12A [12,13].…”
Section: Discussionsupporting
confidence: 89%
“…It is not clear why no radiomodulatory effect was seen in the MCF-7 cell line, given that these cells express as high as 4.5-fold Bcl-2 in comparison with the MDA-MB-231 cells [16,17]. The modest radiation modifying factors seen in all cell lines after pretreatment with the PI3K and mTOR inhibitor (Table 1) are consistent with those reported previously [6], and do not seem to depend on PI3K status, whereas the MCF-7 cells are PI3K mutant [12,13].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…There is evidence to show that inhibition of proteins involved in the PI3K/Akt/mTOR pathway can result in significant radiosensitisation of glioma and breast cancer cells over radiation absorbed doses of up to 8 Gy [15,25,26]. In recent studies, a similar radiosensitisation was demonstrated at 2 Gy in breast and prostate cell lines when pre-treated with inhibitors of HER-2, PI3K and mTOR [21,22]. In this investigation, HER-2 inhibitor (TAK-165) and dual inhibitor of PI3K and mTOR (NVP-BEZ235) were evaluated for their radiomodulatory effects at 6 Gy in 3 breast cell lines.…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, targeting residual HER-2 and downstream signalling components of the EGFR family members may further potentiate the therapeutic benefit of stereotactic radiotherapy for triple-negative breast cancer. It was recently demonstrated that inhibition of phosphoinositide-3-kinase (PI3K) and mammalian target of rapamycin (mTOR) sensitised breast and prostate cancer cells to 2 Gy of radiation, whilst protecting normal prostate cells [21,22].…”
Section: Introductionmentioning
confidence: 99%